The Application of the Show and Tell Technique on English Speaking Skills: An Experimental Study - Annisaa Eka Warliati; Ety Setiawati (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The implementation of the show-and-tell technique is a learning technique that aims to improve English speaking skills actively and productively. This study aims to determine the results of improving the English speaking skills of students of the D4 Hotel Management Study Program at Politeknik Pariwisata Prima Internasional. The method used is a quantitative method with an experimental study (quasi-experimental) control group and experimental group design by comparing the results of the pre-test and post-test of English speaking skills. The implementation of the show-and-tell learning technique has an effect on English-speaking skills, with an increase in the average pretest score before the show-and-tell technique was implemented in the control class of 60.27. In the experimental class the results were 64.30. After the application of the show-and-tell learning technique in both the control and experimental classes, there was an increase; namely, in the control class the average result was 70.87, while in the experimental class the average result was 90.90. With these results, it can be concluded that using the show-and-tell technique has an effect on the average results of English-speaking skills. Therefore, the application of the show-and-tell technique can be implemented in English learning, especially speaking skills.